Implementasi Peraturan Wali Kota Medan Nomor 26 Tahun 2024 Tentang Petunjuk Pelaksanaan Parkir Berlangganan di Tepi Jalan Umum Perspektif Siyasah Dusturiyah - Audina, Yuni; Khalid (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research discusses the implementation of Medan mayor's regulation number 26 of 2024 concerning instructions for implementing subscription parking on the side of public roads from the perspective of siyasah dusturiyyah, namely the concept of constitutional politics in Islam which emphasizes justice, benefit and compliance with the constitution and syar'i values in the administration of government. The aim of this research is to analyze the extent to which the implementation of these regulations is in accordance with the principles of just governance according to Islam, as well as identifying supporting and inhibiting factors for their implementation in the field. This research uses descriptive qualitative methods with a normative juridical approach and field studies. The research results show that this subscription parking policy has positive value in realizing public benefit (maslahah 'ammah) but there are still challenges in its implementation such as lack of socialization, weak supervision, and community resistance due to lack of transparency and accountability. Therefore, efforts are needed to strengthen aspects of public participation, law enforcement and bureaucratic integrity so that the implementation of this policy can be in line with the principles of siyasah dusturiyyah and realize social justice in society.